DESAIN PERENCANAAN PAUD ISLAMI BERBASIS HOLISTIK INTEGRATIF DI RA AL HIDAYAH - Pitria Pebriani (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
This study aims to deeply analyze the alignment between lesson planning and actual classroom implementation in Islamic Early Childhood Education (PAUD), based on the Holistic Integrative (HI) approach. This qualitative case study was conducted at RA Al-Hidayah Ciparay. The data collection process involved various stakeholders, namely one principal, three teachers, and four parents as primary informants. Comprehensive data were collected through participant observation, in-depth interviews, and document analysis, which were subsequently analyzed using thematic coding techniques. The findings reveal that although Islamic teachings and values have been conceptually integrated into the lesson planning documents, a significant operational gap remains. This gap is evident in the formulation of developmental indicators, which lack measurability, and the minimal use of evaluative assessment data in designing subsequent instruction. Consequently, classroom implementation tends to rely more heavily on teachers' personal intuition rather than systematic, empirical data-driven assessments. This study provides a crucial contribution by identifying the root of the operational gap between integrating Islamic values and developmental indicators. It also highlights the urgency of adaptive, assessment-based curriculum alignment to improve the quality of Islamic early childhood education.